Development of a Standard-Based Instrument for Assessing Principal Leadership - Mingchu Neal Luo (The Advocate, 2015)
The purpose of this study is to develop and validate a scale of instrument, the Principal Leadership Index (PLI), to assess principal leadership practices within the framework of ELCC (2011) standards adopted by the Council for the Accreditation of Educator Preparation. Items of the PLI were initially developed by the researcher followed by expert reviews in the field of school leadership and a pilot test. The instrument was used to collect the empirical data from 73 principals, which were investigated with exploratory factor analyses, reliability tests, and multilevel analyses. Results reveal four unique constructs for the leadership dimensions, showing robust psychometric properties with high levels of reliability and validity. The proposed scale can be used for both assessment and professional development to promote principal standard-based leadership behaviors.
Keywords: principal leadership; assessment; standard-based instrument; index development